1980
DOI: 10.1071/ch9800015
|View full text |Cite
|
Sign up to set email alerts
|

The nature of iron in Akaganéite (β-FeOOH)

Abstract: The Mossbauer spectra of a size range of synthetic akaganeite (β-FeOOH) samples containing chloride, and one sample containing fluoride, in the structural tunnels, have been obtained over 4-295 K. At 295 K the spectra consist of overlapping paramagnetic doublets which indicate the presence of at least two sites for iron. Typical parameters for a spectrum of chloride-containing β-FeOOH fitted to two doublets are: (i) δ (relative to iron metal) 0.372 mm s-1, Δ 0.55 mm s-1, Г 0.27mm s-1; (ii) δ 0.375 mm s-1, Δ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…Akageneite, in contrast, is very rare in soils. The conditions for formation of akageneite in the marine environment are favourable, however, as high Cl-(or F-) concentrations are a prerequisite for its formation (Childs et al, 1980;Schwertmann and Cornell, 1991). Murray (1978) found it to be the form of Fe that precipitates from Fe3+ in seawater and suggested (Murray, 1979) that hydrolysis of Fe*+ in seawater may also produce akageneite.…”
Section: Identijication Of Fe Oxides With Dxrd F < Io Fun Fraction)mentioning
confidence: 99%
“…Akageneite, in contrast, is very rare in soils. The conditions for formation of akageneite in the marine environment are favourable, however, as high Cl-(or F-) concentrations are a prerequisite for its formation (Childs et al, 1980;Schwertmann and Cornell, 1991). Murray (1978) found it to be the form of Fe that precipitates from Fe3+ in seawater and suggested (Murray, 1979) that hydrolysis of Fe*+ in seawater may also produce akageneite.…”
Section: Identijication Of Fe Oxides With Dxrd F < Io Fun Fraction)mentioning
confidence: 99%
“…This material was shown to be quite different from any other hydrated iron(II1) oxide or iron(II1) hydroxides that had been reported previously (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). It was concluded that this sample of Fe(OH)3 had an average particle size of -80 P\ in diameter and that the two types of iron environment, visible in the low temperature 57Fe Mossbauer spectrum, were due to surface and bulk iron; the former having a hyperfine field of 437 kOe while the latter, presumably more magnetically ordered, has a field of 486 kOe.…”
Section: By {[C0(11i)(en)(dien)]~o~}[clo~]~ In Aqueous Solution Resultsmentioning
confidence: 89%
“…Among candidates of such atoms or molecules, H 2 O will be most reasonable. Some previous investigations also suggested that H 2 O molecules would occupy some of tunnel sites 8,20) whereas Stahl et al suggested that tunnel sites does not contain water molecules. 13) In their analysis, they assumed that occupation factor, g ¼ 2=3 (they regarded as g ¼ u).…”
Section: Estimation Of U From Rmentioning
confidence: 96%